If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + 6x = 5y Reorder the terms: 6x + 6y = 5y Solving 6x + 6y = 5y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. 6x + 6y + -6y = 5y + -6y Combine like terms: 6y + -6y = 0 6x + 0 = 5y + -6y 6x = 5y + -6y Combine like terms: 5y + -6y = -1y 6x = -1y Divide each side by '6'. x = -0.1666666667y Simplifying x = -0.1666666667y
| 5/y-2/y=-4 | | 8y+12=52 | | -5/2/-1/2-x | | 4y^2=x^2-4 | | P-626/14=25 | | x+2x-5=4x-6 | | 97=12n | | 7/8×50×9/11×15 | | 0=5x^2-x | | -3/-5=7 | | 3x^2+19x+13=0 | | y=x-x+y | | 7=7y+4(y+7) | | 6m^2-26=-m | | 6y+6x=5y+2x | | 4[2t-4]= | | y-1=-7(x+4) | | 12-8t=-52 | | y-2=.16666(x-6) | | -5-2m=9 | | 7(6m-6)+3=-81 | | 8t-16= | | 2x+8=14x+12 | | y=t+t-y | | 3(-40+-2r)+20= | | y-2=.10(x+10) | | 2•-4/5 | | 6-4(2x+8)=16 | | (t-3)7=6+21 | | 6x-13=90 | | 8[t-2]= | | 4v+4=4 |